Jenis-Jenis Skala dan Teknik Skoring dalam Penilaian Psikomotorik pada Mata Pelajaran Pendidikan Agama Islam - Sabrina Septiani; Ramadhan Reza; H. Akil; Abdul Aziz (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
his research aims to identifiy various of attitude scales and psychomotor assessment techniques within the context of learning. The method used is a quantitative approach through library research. The data sources were obtained through a review of literature from academic journals, reference books, and various instructional documents that present numerical data related to the practice of assessing attittudes and skills. The objects of study in this research include types of attitude scales, such as the Likert scale, Guttman scale, and Semantic Differential scale, as well as psychomotor assessment techniques, including performance observation, performance appraisal, and the use of rubrics. Data analysis was carried out using descriptive quantitative methods by presenting how frequently each model is used and the tendency of its effectiveness as reflected in various literature findings. Based on the research resulth, the Likert scale is the most commonly used to evaluate students attitudes, while in the assessmentnof psychomotor aspects, performance observation is the primary technique of choice.